Herança de caracteres agronômicos e efeito da época de semeadura sobre desempenho da soja - Mattos, Thúlio Pereira (2018)
The breeding programs seek to develop cultivars that are more productive, resistant to pests and diseases, with broad adaptation and greater stability, for different sites and types of cultivation. Thus, the inheritance study for productivity and agronomic traits favorable to higher yields for soybean cultivation contributes to the supply of estimates of the genetic parameters, which are primordial for the choice of methods used in the initial and advanced stages of selection. The sowing season is one of the most important factors for soybean yield. This dissertation is subdivided into: literature review about soybean crop and breeding, genetic parameters and sowing times, and two chapters. In the first chapter, a research was carried out to determine the inheritance of characters related to productivity and agronomic traits in a soybean segregating population from contrasting parents. The experiment was carried out in august of 2017 at the Capim Branco farm of UFU. The P1, P2, F1 and F2 generations were evaluated from the two-parent crosses between cultivars MG / BR46 Conquista and Emgopa 316. High heritability coefficients were found, varying from 80.68 to Number of maturing nodes at 96.82 for number of days in flowering. In the population F2, the existence of transgressive segregants for all the characters was verified. The genetic variance and the heritability of the agronomic characters of the F2 population, from the hybridization of MG / BR 46 Conquista and Emgopa 316, allows to obtain gains of selection of superior individuals mainly for number of pods and productivity, characters linked directly productivity. In the second chapter, we aimed to study the effect of sowing season in the Uberlândia MG region. At the experimental station of the Capim Branco farm of the Federal University of Uberlândia (UFU), 12 soybean cultivars were evaluated in a randomized block design with four replicates, in which agronomic and productivity and grain characteristics were evaluated. It was observed that sowing in October and November contributed to high yields. Considering the out - of - season sowing recommended for the region, in December and January, conventional cultivars BRSMG 68 and TMG 801 had their productivities less affected. By Eberhart and Russel (1966) and Centroid methods the wide adaptation, high productivity and stability factors were UFUS 7415, BRS 7270 IPRO and CD 2737 RR.